Correlation of serum lipid profile and diabetic retinopathy: a prospective study - Hemalatha, K.; Preethi, V.; Babu, Manohar (International Journal of Research in Medical Sciences, 2025)
Background: To correlate serum lipid levels and presence of Diabetic Macular edema in diabetic retinopathy patients. To compare the serum lipid profile of patients with and without Diabetic Macular edema. To compare and analyze the present study with reference to other studies on serum lipid profile in diabetic retinopathy. To emphasize the importance of doing serum lipid profile as routine investigation in patients with diabetic retinopathy and to initiate treatment for those appropriate. Methods: A prospective cross-sectional study conducted at Tertiary Eye Care Centre, Salem, TamilNadu with petients presenting to Retina clinic for 6 months with a sample size of 186. Results: The data analysis was performed using statistical software package SPSS version 22.0. Both the descriptive and inferential statistics were used. The continuous variables were summarized as mean with standard deviation. The categorical variables were summarized as frequencies and proportions. The comparison of continuous variables was done using unpaired ‘t’ test and comparison of categorical variables were done using Chi square test or Fisher’s exact test depending on distribution. P value of less than 0.05 was considered significant. Conclusions: The present study gives good evidence of a significant correlation between higher levels of total cholesterol, LDL-C, HbA1C and lower levels of HDL-C with the presence of Diabetic Macular edema. Hence along with diabetes control drugs, lipid lowering drugs should be started for diabetic patients having dyslipidemia.